Hubungan Tingkat Pengetahuan Tentang Vulva Hgiene dengan Kejadian Pruritus Vulva Pada Saat Menstruasi Di SMP PGRI Kasihan Bantul - Dwanisya, Joshan; Tri Setiyaningsih, Yanita (HEALTHY BEHAVIOR JOURNAL, 2023)
Background: Adolescence is often said to be the transition period from childhood to adulthood, where the reproductive organs become physically, socially, and psychologically mature. These changes occur when two hormones, estrogen and progesterone, begin to work properly. One of the characteristics of puberty in adolescent girls is the start of menstruation. Objective: The purpose of this study is to determine the relationship between the level of knowledge about vulva hygiene and the incidence of vulvar pruritus during menstruation at SMP PGRI Kasihan Bantul. Method: This research is a quantitative research that uses correlation analysis with a cross sectional research design. The population in this study was 73 grade VII and VIII teenage girls, taken using total sampling technique. The measuring instrument used a knowledge of vulva hygiene questionnaire and the incidence of pruritus vulva. The data analysis used univariate and bivariate using Somer’s d test. Result: The results of the study said that the majority of young women at SMP PGRI Kasihan Bantul had a level of knowledge about vulva hygiene included in the sufficient category of 43 female students 58.9%. Young women at SMP PGRI Kasihan Bantul who experience vulvar pruritus are included in the medium category as many as 43 female students 58.9%. Conclusion: There is a relationship between the level of knowledge about vulva hygiene and the incidence of vulvar pruritus in SMP PGRI Kasihan Bantul with a p value of 0.011. There is a closeness between the level of knowledge about vulva hygiene and the incidence of vulvar pruritus in SMP PGRI Kasihan Bantul with an r value of -0.240.